2018
DOI: 10.1016/j.worlddev.2017.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Conditional cash transfers for primary education: Which children are left out?

Abstract: Highlights We investigate predictors of child participation in Bolivia’s CCT program. Children less exposed to Westerners have lower probabilities of receiving transfers. Participation rates are highest around age 11 y. Parents’ modern human capital is not associated with participation. Participation rates are similar for boys and girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Evaluating the impact of our hypothetical program on poverty reduction is beyond the scope of our paper, but it seems that, in our setting, an unconditional cash transfer would be preferable. Bauchet et al (2018) reached a similar conclusion when observing that, in Bolivia, the most marginalized group of children was less likely to participate in educational…”
Section: Simulation Of the Effect Of A Conditional Cash Transfermentioning
confidence: 65%
“…Evaluating the impact of our hypothetical program on poverty reduction is beyond the scope of our paper, but it seems that, in our setting, an unconditional cash transfer would be preferable. Bauchet et al (2018) reached a similar conclusion when observing that, in Bolivia, the most marginalized group of children was less likely to participate in educational…”
Section: Simulation Of the Effect Of A Conditional Cash Transfermentioning
confidence: 65%
“…For example, using a sample of 811 children between 7 and 16 years of age, Bauchet et al. () found that child age is significantly positively related to the participation in the conditional cash transfer program in Bolivia.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with the findings in previous studies. For example, using a sample of 811 children between 7 and 16 years of age, Bauchet et al (2018) found that child age is significantly positively related to the participation in the conditional cash transfer program in Bolivia. Children's and adolescents' education level is also a significant determinant of the CSP exit.…”
Section: Factors Influencing the Csp Exitmentioning
confidence: 99%
See 1 more Smart Citation
“…CCT is a policy that requires beneficiaries to carry out various requirements, such as sending children to school, regularly checking up with a doctor, so that the beneficiaries can receive the benefit in cash. Ganimian and Murnane (cited in Bauchet et al 2018) state the impact of CCT program on academic and cognitive skills remained unclear. Thus, even though the level of education is increased, the study found mixed result on the outcome of education process that is measured by increase in cognitive skills.…”
Section: An Inconvenient Truth: Why Social Policies Might Failmentioning
confidence: 99%